Descriptive Study on Students' Grammar Ability in Writing Recount Text - Ayu Amelia Lihawa; Sri Widyarti Ali; Fahira Malabar (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The objective of this research is to identify the students’ grammar ability in writing recount text. The grammar is limited on the use of past tense, especially in using past verb. The Subjects of this research are the students in class X IPA 3 of SMA NEGERI 1 GORONTALO that consist of 20 students. The method of this research is qualitative method. The result of this research presents the students' correct verb in using past verb in recount text. As the result, the total of students’ correct verbs is 157 with percentage 61% and the total of students incorrect verbs are 101 with percentage 39%. Therefore, the percentage of students’ ability is 61% and can be classified into high level in intensity 61% - 80%. Hence, it is suggested that the school and teachers should provide the appropriate method or strategy which can support the learning process to improve students' motivation and interest in writing recount text.